THE EFFECT OF AUDIOVISUAL METHOD ON STUDENTS’ SPEAKING ACHIEVEMENT AT SMPN 2 KENDARI - Anggriani, Andi Dina; Suhartini, Lelly; Fatmawati, Wa Ode (Universitas Halu Oleo, 2020)
This study aims to find out whether there is a significant effect of applying audio-visual method on students’ Speaking achievement of second grade students at SMPN 2 Kendari or not. Population of this research is the entire second grade class in academic year 2017/2018 of SMPN 2 Kendari. The total numbers of the population are 280 students where class VIII B as experimental class and VIII A as control class were chosen as the sample of this study used purposive sampling technique. This study applied quasi-experimental design which concerned on two groups; they are control group and experimental group. These two groups received a different treatment. The implementation of audio-visual method was applied on experimental class. The data which analyzed in this study was quantitative data; it gained from the pretest and posttest result of the two classes which analyzed using descriptive statistic and inferential analysis (Independent sample t-test). The result shows that the gain of the mean score of experimental class 1.76 is higher than the gain score of control class 0.57. It shows that teaching speaking by Audiovisual method in the experimental class has a better effect in enhancing students’ speaking achievement. Then the result of hypothesis testing showed that the value of Sig. (2-tailed) is 0.044 which smaller than (<0.05). Hence, it can be concluded that H0 is rejected and H1 is accepted which means that there is significant effect of Audiovisual method on students’ speaking achievement at eight grade of SMP N 2 Kendari. Keywords: Speaking, Audiovisual, Learning method